C IV Broad Absorption Line Variability in QSO Spectra from SDSS Surveys - De Cicco, Demetra; Brandt, William N.; Grier, Catherine J.; Paolillo, Maurizio (Frontiers in Astronomy and Space Sciences, 2017)
Broad absorption lines (BALs) in the spectra of quasi-stellar objects (QSOs) are thought to arise from outflowing winds along our line of sight; winds, in turn, are thought to originate from the accretion disk, in the very surroundings of the central supermassive black hole (SMBH), and they likely affect the accretion process onto the SMBH, as well as galaxy evolution.\\ BALs can exhibit variability on timescales typically ranging from months to years. We analyze such variability and, in particular, BAL disappearance, with the aim of investigating QSO physics and structure.\\ We search for disappearing C {\scriptsize{IV}} BALs in the spectra of 1319 QSOs from different programs from the Sloan Digital Sky Survey (SDSS); the analyzed time span covers $0.28-4.9$ yr (rest frame), and the source redshifts are in the range $1.68-4.27$. This is to date the largest sample ever used for such a study.\\ We find 67 sources ($5.1_{-0.6}^{+0.7}$\% of the sample) with 73 disappearing BALs in total ($3.9_{-0.5}^{+0.5}$\% of the total number of C {\scriptsize{IV}} BALs detected; \textbf{some sources have more than one BAL that disappears}). We compare the sample of disappearing BALs to the whole sample of BALs, and investigate the correlation in the variability of multiple troughs in the same spectrum. We also derive estimates of the average lifetime of a BAL trough and of the BAL phase along our line of sight.